Emerging Delivery Strategies of Platelet-Rich Plasma with Hydrogels for Wound Healing - Ya Zhang; Zi-Lin Wang; Ze-Peng Deng; Zi-Li Wang; Fei Song; Li-Li Zhu (Advances in Polymer Technology)
Platelet-rich plasma (PRP), a platelet-rich plasma concentrate obtained from whole blood, has been widely used to treat wounds due to its high contents of growth factors that can not only play a role in the hemostasis, repair, and anti-infection of wounds but also promote cell proliferation, maturation, and angiogenesis. However, after PRP activation, its clinical effect was limited because of burst and uncontrolled release of growth factors and poor mechanical properties of PRP gels. In recent years, increasing attention has been moved to the loading and sustained release of growth factors in PRP by polymeric carriers. Hydrogels, as an interesting carrier, enable controlled delivery of growth factors by structural designs. Moreover, using hydrogels to encapsulate PRP is favorable to controlling the mechanical properties and water maintenance of PRP gels, which can provide a stable and moist wound repair environment to promote coordinated operations of skin tissue cells and cytokines as well as wound healing. In this review, the state of the art of hydrogels that have been used to load PRP for wound treatments is introduced, and further prospects in the research area are proposed.